Język wstrętu jako narzędzie społecznych regulacji. Wstępny zarys problemu. - Nasalski, Ignacy (Stylistyka, 2021)
Among all human emotions disgust plays an extraordinary role, primarily because it affects social relationships, shapes moral judgments, influences political beliefs as well as many other cultural and religious phenomena. Despite its significance and the richness of the linguistic means with which it is expressed, the communication linguistic aspects of disgust have not yet been satisfactorily described. This text is an attempt to fill this gap. The author introduces the concept of „language of disgust” as a specific functional variation of language and goes on to describe its properties, the scope as well as functions which communicating disgust serves.